External Ear Alveolar Subtype Rhabdomyosarcoma : A Rare Case Report - Wilfred, Rebecca; Saad, Sazafi; Tang, Ing Ping (Gazi Universitesi, 2022)
External ear canal (EAC) childhood rhabdomyosarcoma is rare and aggressive due to their potential intracranial spread and meningeal involvement. Given its nonspecific presentation such as bloody otorrhoea,otalgia and aural polyps,it is commonly misdiagnosed as chronic otitis media ,thereby delaying diagnosis. Here we report a rare occurrence of EAC alveolar subtype rhabdomyosarcoma in a 7-year-old boy.